Freedom of religion and law of apostasy in Malaysia / Nurjeehan Abd Jabar, Eileys Ismail and Zahida Azmah Ishak. - Abd Jabar, Nurjeehan; Ismail, Eileys; Ishak, Zahida Azmah (2006)
The main aim of this study is to find some answers as regards to the right to profess and practice the religion according to Islamic perspective and the Federal Constitution as compared to law of apostasy in Malaysia. In order to do this, we shall examine the general Quranic provisions, hadith and Islamic jurist view in comparing to Federal Constitution as regards to freedom of religion. It must be noted that the law of apostasy has been legislate by some states into their state law such as Section 13 of the Criminal Law Enactment of 1992. The main question that we hope to answer in this research is; firstly, whether individual right to profess and practice religion is protected under Article 11 of the Federal Constitution. Secondly, whether the implementation of apostasy law in Malaysia will be constitutional and finally, whether Sharia' Court is the competence court in deciding the apostasy cases.